2014
DOI: 10.1038/jcbfm.2014.106
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Steal Phenomenon is an Incomplete Contributor to Negative Cerebrovascular Reactivity in Patients with Symptomatic Intracranial Stenosis

Abstract: 'Vascular steal' has been proposed as a compensatory mechanism in hemodynamically compromised ischemic parenchyma. Here, independent measures of cerebral blood flow (CBF) and blood oxygenation level-dependent (BOLD) magnetic resonance imaging (MRI) responses to a vascular stimulus in patients with ischemic cerebrovascular disease are recorded. Symptomatic intracranial stenosis patients (n ¼ 40) underwent a multimodal 3.0T MRI protocol including structural (T 1 -weighted and T 2 -weighted fluidattenuated invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Such a blood-stealing phenomenon has been observed in ischemic stroke, and ischemic cerebrovascular disease. [30][31][32] Attenuated CBF responses to vasodilation have been reported using both the CCI 33,34 and fluid percussion injury models. 35 However, negative CBF responses to hypercapnia have not been reported previously.…”
Section: Cortical Blood Flowmentioning
confidence: 99%
“…Such a blood-stealing phenomenon has been observed in ischemic stroke, and ischemic cerebrovascular disease. [30][31][32] Attenuated CBF responses to vasodilation have been reported using both the CCI 33,34 and fluid percussion injury models. 35 However, negative CBF responses to hypercapnia have not been reported previously.…”
Section: Cortical Blood Flowmentioning
confidence: 99%
“…The third and last study, which found a higher CVR ipsilaterally, was the study by Altamura et al [21] who attributed this to the decreased fMRI signal detection in hemodynamic impaired patients resulting in more noise within the data. A reason as to why studies could find a higher CVR ipsilaterally could be cerebral metabolic rate of oxygen (CMRO 2 ) upregulation in the ipsilateral hemisphere [48] . CMRO 2 upregulation can be caused by a hypercarbic hyperoxia stimulus (carbogen) in which the tissue that is hypoxic at baseline metabolizes the additional oxygen provided and therefore artificially decreases the relative amount of dHb being present, thus creating a falsely increased CVR.…”
Section: Bold and Asl Cvr Results In Cerebrovascular Diseasementioning
confidence: 99%
“…In healthy parenchyma, CVR primarily derives from a large increase in cerebral blood flow (CBF) and volume (CBV) in response to a vasostimulatory agent such as carbon dioxide (i.e., hypercapnia). Significantly diminished or negative changes in CVR after during hypercapnia have previously been shown to correlate with regions affected by prior infarct and symptomatology 1,26,30 . However, owing to the relative novelty of hypercapnic CVR mapping using MRI compared to more established clinical measures such as acetazolamide SPECT, interpretation of hypercapnic CVR maps has not been standardized.…”
Section: Introductionmentioning
confidence: 91%
“…Cerebrovascular reactivity (CVR) is a well-documented and valuable surrogate marker of cerebrovascular reserve in patients with previously identified intravascular pathology 1,9,10,12,13 . In healthy parenchyma, CVR primarily derives from a large increase in cerebral blood flow (CBF) and volume (CBV) in response to a vasostimulatory agent such as carbon dioxide (i.e., hypercapnia).…”
Section: Introductionmentioning
confidence: 99%